Estrategia de muestreo usando estimadores de regresión generalizada para la estimación de tasas de favoritismo en elecciones presidenciales en Colombia (2009)
Six favoritism rate estimators for presidential elections, which use GREG estimators in the ﬁrst stage of sampling, are proposed. Its performance is evaluated with Monte Carlo Simulation and by the variation coeﬃcient, calculated for the 2006 Presidential elections case, using the results from 2002 as auxiliary information. It is found that the estimators proposed don’t have attributes which makes them better than the totals pi-estimators quotient.